KONTRIBUSI GAYA MENGAJAR, KOMUNIKASI DAN INTERAKSI GURU TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS XII IPA SMA DI KABUPATEN PASAMAN BARAT - Arfianti, Fina; Lufri, Lufri; F, Farida (Kolaboratif, 2014)
This article was written to determine the contribution of the teacher's teaching style on learning outcomes of students of biology, contributes to the teacher communication in the learning outcomes of students of biology, contribution to the teacher interaction in the learning outcomes of students of biology, contribution of teaching styles, communication and interaction of the teacher in the learning outcomes of students learning biology class XII Science High School in West Pasaman academic year 2013/2014. Data were analyzed manually, by trimming path model analysis. Individually testing each variable obtained t count> t table. That is, there is the contribution of each independent variable on the learning outcomes of students of class XII science biology high school in West Pasaman. Obtained simultaneous testing of Fcount> Ftable. That is, there is a contribution of teaching styles, communication, and interaction of the teacher in the learning outcomes of students learning biology class XII Senior High School in West Pasaman.